Effects of myofascial release applied to neck muscles and craniocervical flexor training in patients with chronic myofascial TMD: A single arm study - Calixtre, Letícia Bojikian [UNESP]; Rezende, Monica Ambiel; Kamonseki, Danilo Harudy; Beatriz de Oliveira, Ana (Elsevier, 2021)
Objective: To evaluate the effects of myofascial trigger point release applied to superficial neck muscles and strengthening of the deep flexor muscles in subjects with myofascial temporomandibular disorders (mTMD). Methods: Fourteen women (23.4 ± 3.32 years old) presenting with mTMD and trigger points (TrPs) in the sternocleidomastoid, suboccipital, and upper trapezius muscles were included in this study. They were evaluated on two occasions during a baseline period (3 weeks apart) with no intervention and a third time after a 5-weeks intervention protocol. Outcome measures included pressure pain threshold (PPT) over the masticatory muscles, mandibular function, orofacial pain intensity, maximum mouth opening, and the craniocervical flexion test. All women received 10 treatment sessions that included strain-counterstrain technique applied to TrPs found in the prior listed superficial neck muscles and stabilization exercise using a pressure biofeedback for the deep neck flexor muscles. One-way ANOVA or correspondent non-parametric tests as well as effects sizes were used to compare the outcomes at baseline and after the treatment. Results: Statistically significant improvements were found in the PPT over left masseter and temporalis (p < 0.05) (mean difference (MD) of 0.50 and 0.42 kg/cm2), orofacial pain intensity (MD = −3.39 points), mandibular function (MD = −7.22 points) and performance of the deep cervical muscles (MD = 130.42 points) compared to baseline period. Effect sizes were moderate or large. Conclusion: The protocol intervention may have positive effects in patients with mTMD. However, studies with better methodological quality need to be performed to confirm those effects. Registration: ensaiosclinicos.gov.br (RBR-7x828q);
Keywords: Exercise; Manual therapy; Neck muscles; Temporomandibular dysfunction